M. Business - O.C. Ferrell; Geoffrey Hirt; Linda Ferrell (USA McGraw Hill, 2019)
The business world can be hazy-tough to navigate and understand. With obstacles put in place to question a potential leader's ethics, world view and career outlook, how does a future leader rise to the top while overcoming obstacles? "M: Business" brings clarity to what business is about. Its design provides a "cutting edge approach" to business, and its technology components offer an "active learning environment," allowing students to envision a prosperous career in business.
Age Group: Adult
Keywords: Introduction to business management